2008
DOI: 10.1063/1.3005864
|View full text |Cite
|
Sign up to set email alerts
|

Biglobal linear stability analysis for the flow in eccentric annular channels and a related geometry

Abstract: Recently, it has been observed that simple geometry characterized by a low level of symmetry present interesting peculiarities in the process of transition from laminar Poiseuille flow to turbulent flow. Examples of this type of geometry are eccentric channels and, more generally, parallel channels containing a narrow gap. In the present work, a global linear stability analysis for the flow in this class of geometry has been performed. The problem is discretized through spectral collocation and the eigenvalue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…We perform the BiGlobal stability analysis on this duct Poiseuille flow with parameters Re = 100, β = 1, and A = 1 and 2 to be consistent with the works by Theofilis et al 40 and Merzari et al 21 A uniform mesh is used for this verification, with the spatial resolution ranging from 32 2 to 256 2 for the square duct (A = 1), and from 64 × 32 to 512 × 256 for the rectangular one (A = 2). The eigenvalue spectra for the plane Poiseuille flow (PPF) at Re = 100 is computed by solving the Orr-Sommerfeld equation corresponding to the extreme case A → ∞.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We perform the BiGlobal stability analysis on this duct Poiseuille flow with parameters Re = 100, β = 1, and A = 1 and 2 to be consistent with the works by Theofilis et al 40 and Merzari et al 21 A uniform mesh is used for this verification, with the spatial resolution ranging from 32 2 to 256 2 for the square duct (A = 1), and from 64 × 32 to 512 × 256 for the rectangular one (A = 2). The eigenvalue spectra for the plane Poiseuille flow (PPF) at Re = 100 is computed by solving the Orr-Sommerfeld equation corresponding to the extreme case A → ∞.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The BiGlobal stability analysis method is proposed to take the advantage of this feature by assuming the perturbation in the form of a normal mode in the spanwise direction, thus the primary perturbation characteristics in the cross-sectional (x-y) plane are preserved and the computational cost is significantly reduced. The BiGlobal linear stability analysis has been employed for a number of physical problems, such as the flow in a channel, [19][20][21][22] over a backward-facing step [23][24][25] or a bluff body. 26 It has also been employed for the problem of flow past an isolated airfoil.…”
Section: Introductionmentioning
confidence: 99%
“…Additional results concerning the POD of computational data for this geometry are available in Merzari et al [3]. In particular, it is remarkable that the most energetic mode of turbulence (k = 2, m = 1) is very similar in shape to the most unstable eigenmode found by the linear stability analysis of Merzari et al [4].…”
Section: Pod Of Cfd Datamentioning
confidence: 66%
“…At higher Reynolds numbers coherent structures are observed on the border of the gap. This behaviour might be related to a bifurcation of the laminar steady state that has been observed both computationally and experimentally [4,5]. In fact, experimental results [5] have shown that the onset of the transition to turbulence in geometries containing a narrow gap is characterized by a strong oscillatory behavior of the cross velocity in the gap region [6].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation